Penerapan Lumi H5P dalam Media Pembelajaran Matematika pada SDK PERO Menggunakan Metode MDLC - Maria Imakulata Ina Talu; Stefanus Dwi Istiavan Mau; Lidia Lali Momo (Modem : Jurnal Informatika dan Sains Teknologi., 2025)
This research is entitled “Implementation of Lumi H5P in Mathematics Learning Media at SDK PERO Using the MDLC Method.” The aim of this research is to create a digital-based interactive learning medium designed to enhance students’ understanding of the subject matter. media that can help students understand mathematics lessons, particularly on the topics of whole numbers and multiples, in an engaging and easy-to-understand way. The approach applied in this research is the MDLC method.. Each stage was carried out systematically to produce an interactive and high-quality learning media. The learning media application was developed using LUMI H5P, which provides various interactive features such as text, images, videos, and interactive exercises in the form of single choice sets and drag-and-drop activities. The results of the study show that the implementation of Lumi H5P-based learning media can increase students’ learning interest and facilitate their understanding of the material. Moreover, the simple interface design and user-friendly features make this application effective for both classroom learning and independent study. Therefore, the implementation of Lumi H5P in mathematics learning The media can act as an innovative solution to promote a learning process that is more engaging and effective.